Fish-oil esters of plant sterols improve the lipid profile of dyslipidemic subjects more than do fish-oil or sunflower oil esters of plant sterols - Demonty, Isabelle; Chan, Yen-Ming; Pelled, Dori; Jones, Peter JH (The American journal of clinical nutrition, 2006)
BACKGROUND: Fish-oil fatty acid esters of plant sterols (FO-PS) were shown to have hypotriglyceridemic and hypocholesterolemic properties in animal models. OBJECTIVE: The objective of the study was to evaluate the hypolipidemic effects of FO-PS supplementation in healthy hypercholesterolemic persons fed an olive oil (OO)-based diet. DESIGN: Twenty-one moderately overweight, hyperlipidemic subjects participated in a semi-randomized, single-blind, 4-period crossover study including 4 experimental isoenergetic diets of 4 wk each and 4-wk intervening washout periods. Diets contained 30% of energy as fat, of which 70% was from extra-virgin OO, and differed only in the supplement oil: OO, fish oil, FO-PS, or sunflower oil esters of plant sterols (SU-PS). Both fish oil and FO-PS provided 5.4 g total eicosapentaenoic and docosahexaenoic acids/d. FO-PS, SU-PS, and OO provided the equivalent of 1.7, 1.7, and 0.02 g free plant sterols/d, respectively. RESULTS: Fish oil and FO-PS resulted in fasting and postprandial plasma triacylglycerol concentrations that were markedly lower than those observed with OO and SU-PS (P = 0.0001), but to a different extent. LDL cholesterol was significantly lower after supplementation with FO-PS and SU-PS than at the end of the control OO diet (P = 0.0031 and 0.0407, respectively). HDL cholesterol was not affected. FO-PS and SU-PS resulted in a lower ratio of total to HDL cholesterol and lower apolipoprotein (apo) B concentrations than did OO and fish oil. The ratio of apoB to apoA was significantly lower after SU-PS consumption than after consumption of OO (P = 0.0126) and fish oil (P = 0.0292). FO-PS and SU-PS resulted in similar ratios of apoB to apoA. HDL₂ and the ratio of HDL₂ to HDL₃ were significantly higher at the end of the FO-PS treatment than at the end of the OO (P = 0.0006), fish oil (P = 0.0036), and SU-PS (P = 0.0016) treatments. CONCLUSION: Supplementation of an OO-based diet with FO-PS may reduce cardiovascular disease risk more than does supplementation with fish oil or SU-PS.